First report of the invasive Australian tortoise beetle Trachymela sloanei (Blackburn, 1897) (Coleoptera: Chrysomelidae) in Algeria - Hadiby, Rached; Boukheroufa, Mehdi; Vitali, Francesco; Sakraoui, Feriel; Frih, Abdelaziz; Benhacene, Racha; Benotmane, Kamelia Hesni; Adjami, Yasmine (Zootaxa, 2025)
Trachymela sloanei (Blackburn, 1897) (Coleoptera: Chrysomelidae: Chrysomelinae), a leaf beetle native to Australia and recognized as a defoliator of Eucalyptus spp. (Myrtaceae), is reported for the first time from Algeria and the African continent. In May 2025, 20 adults were collected from Eucalyptus camaldulensis in the urban area of Sidi Amar (Annaba, northeastern Algeria), where characteristic foliar damage and feeding traces were observed. Identification was confirmed using diagnostic morphological characters. Field evidence indicates a reproducing population actively feeding on ornamental Eucalyptus trees. Considering its invasive history elsewhere, this detection highlights the risk of further spread and potential impacts on Eucalyptus plantations and urban greenery in North Africa. The present record expands the known distribution of T. sloanei and underscores the need for continued surveillance of Eucalyptus-associated pests in the Mediterranean region.